Road Geometry Planning on Horizontal Curves Using AutoCAD® Civil 3D: A Case of Mujahiddin – Lampok Road, Nusa Tenggara Barat - Bayu Endoriawan; Yusra Aulia Sari (LEADER: Civil Engineering and Architecture Journal, 2023)
Indonesia is a country that has a large forest area, making it famous for its wood industry. The wood industry is processed into various kinds of furniture to be exported to all cities and countries. The connecting road between Mujahiddin-Lampok Road is made to support the economic activities of residents as Copper and gold suppliers. This research aims to design road geometrics, especially horizontal alignments by the "2021 Road Geometric Design Guidelines". The road to be made starts from STA 0+000 to STA 1+423.75 with objective data in 2022 using the AutoCAD® 3D auxiliary program. This road planning uses quantitative data which is divided into primary and secondary data. From the calculation results it can be concluded that on the 1424 km long road 2 different types of curves can be applied. The types used are SCS and SS (Road geometric planning must consider cost efficiency and safety.